MELHORIAS DO DESEMPENHO TÉRMICO EM RESIDÊNCIAS DE PALAFITA DE MADEIRA PARA OCUPAÇÃO DE ÁREAS ÚMIDAS NA CIDADE DE MACAPÁ-AP - Kuwahara, Letícia; Carvalho, Victória; Silva, Marcelle Vilar da (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The study presents an alternative social housing model applicable to the scenario of irregular occupation in wetlands located within the urban perimeter of the city of Macapá. The high temperatures recorded in the city (due to being at 0 ° latitude) emphasize the relevance of the search for a model with bioclimatic suitability that allows greater thermal comfort inside the residences. In addition, the intense levels of occupation and degradation of the humid areas of the city are alarming, so a moderate alternative is proposed between the social context involved, the conservation of the still existing natural environment and the economic factor. In this way, the constructive typology chosen for the proposal is an adaptation of the vernacular architecture found in this region of the Amazon, which has a greater feasibility of execution and applicability. The study also intends to work with the deconstruction of the stereotype of unhealthiness existing in relation to the constructive techniques in wood, by means of the application of the technical parameters of environmental comfort and sustainability in the dwellings generating data of proof of the energy efficiency of the typology palafítica.